PENERAPAN MODEL ARGUMENT DRIVEN INQUIRY UNTUK MENGETAHUI TINGKAT PERBEDAAN KEMAMPUAN BERPIKIR KRITIS ANTARA SISWA LAKI-LAKI DAN PEREMPUAN PADA MATERI CAHAYA KELAS VIII DI SMP IT AL-FITYAH - Salsadila Safitri; Zulhelmi Zulhelmi; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The ability to think critically is one of the competencies that must be possessed by students. The low ability to think critically becomes a problem that must be solved. Gender differences are one of the factors that influence in the formation of critical-thinking characters. To develop students' critical thinking skills, it is necessary to innovate learning by applying one of the learning models, namely the ADI learning model. This study aims to determine the effect of the application of the ADI learning model on the critical thinking skills of male and female students and to determine the level of differences in critical thinking skills between male and female students in classes using the ADI learning model. The type of research conducted is comparative descriptive using the One Shoot Case Study Design. The samples taken were class VIII A male students, totaling 22 students, and class VIII B female students, totaling 27, where the two classes consisted of two experimental classes. The data collection instrument was a test of the results of critical thinking skills for class VIII light material which consisted of 6 description questions. The data analysis used is descriptive analysis through the level of critical thinking skills and inferential analysis through normality test, homogeneity test, and Independent T-Test test with the help of SPSS version 23. The results showed that the student’s critical thinking skills using the ADI learning model were categorized as sufficient. The average height obtained by male students is 72.45 while female students are 69.29, while the results of inferential analysis obtained using SPSS are that there is a difference in the level of critical thinking abilities of male and female students using the ADI learning model (sig. ) 0.039 < 0.05 where the results can be concluded that the critical thinking ability of men is taller than women.Keywords: Argument Driven Inquiry, Critical Thinking Skills, Male and Female